Towards refining microstructures of biodegradable magnesium alloy WE43 by spark plasma sintering. (15th October 2019) - Soderlind, Julie; Cihova, Martina; Schäublin, Robin; Risbud, Subhash; Löffler, Jörg F.
Graphical abstract: Abstract: Microstructural refinement of magnesium (Mg) alloys is beneficial for mechanical and corrosion properties, both of which are critical for their successful application as temporary implant materials. One method of achieving a refined microstructure is through rapid solidification via gas-atomization-powder production. In this study we investigated spark plasma sintering (SPS) as a potential processing method for maintaining this refined microstructure while achieving a range of porosities up to full densification. We characterized the microstructural evolution as a function of sintering temperature from 250 to 450 °C for the alloy WE43 using multi-scale correlative microscopy techniques, including light microscopy and scanning and transmission electron microscopy-based methods. The spatial distribution of the two major alloying elements, neodymium (Nd) and yttrium (Y), was determined and the intermetallic phases they form identified using energy dispersive X-ray spectroscopy in conjunction with electron diffraction. The gas-atomized powder microstructure consists of Mg-rich dendrites and a percolating interdendritic Mg–Nd–Y ternary phase with structure Mg14 Nd2 Y, surrounded by a high Nd and Y content in solid solution. This microstructure is maintained up to a sintering temperature of 350 °C, while with higher sintering temperatures segregation of Nd and Y dominates. The percolating ternary phase breaks up into faceted globular precipitates with structure Mg5 Nd, which is isomorphous to Mg14 Nd2 Y. Y comes out of solution and migrates to previous powder-particle surfaces, possibly forming Y2 O3 . Sample densities ranged from 64 to 100% for sintering temperatures of 250 to 450 °C, respectively, and the grain size remained constant at about 10 µm. SPS is demonstrated to be an attractive alternative method for processing Mg alloys to a wide range of porosities and fine microstructures. The microstructural refinement achieved by SPS holds the potential for slow and homogeneous corrosion. Statement of Significance: This study presents the impact spark plasma sintering (SPS) has on the microstructure of WE43, a magnesium alloy used for biodegradable implants. SPS is of great interest in this context as it is scalable, rapid, and has the potential for tuning density while maintaining a refined microstructure. The microstructure and density are explored from the gas-atomized powder to the densified material using electron microscopy and chemical mapping from the macro- to the nano-level. The insights gained reveal an original evolution of rare-earth element distribution with an isomorphous chemistry change, while the microstructure develops from the non-equilibrium state (powder) towards an equilibrium structure upon sintering. This study, including measurements of mechanical performance, sets the premises of SPS for the fabrication of Mg-based implants with tunable characteristics.